The blood pressure targets in sepsis patients with acute kidney injury: An observational cohort study of multiple ICUs - Zhao, Lina; Fan, Yan; Wang, Zhiwei; Wei, Zhiyong; Zhang, Ying; Li, Yun; Xie, Keliang (Frontiers in Immunology, 2022)
Abstract Background: The maintenance of blood pressure is pivotal in preventing sepsis with acute kidney injury (AKI). Especially in sepsis patients treated with vasopressors. The optimal the blood pressure has been controversial to maintain renal perfusion. This study aims to explore the blood pressure target in sepsis with AKI. Methods: We retrieved patient data from the MIMIC IV and eICU databases. The Lasso regression model was used to identify the relationship between blood pressure and sepsis in patients with AKI and remove collinearity among variables. Generalized additive models were used to estimate the blood pressure range in patients with sepsis with AKI. Statistical methods such as multivariable logistic regression, propensity score analysis, inversion probability-weighting, and doubly robust model estimation were used to verify the target blood pressure for patients with sepsis and AKI. Results: In total, 17874 patients with sepsis were included in this study. The occurrence of sepsis in patients with AKI was influenced by both mean arterial pressure (MAP) and diastolic blood pressure (DBP). The range of MAPs and DBPs may be 65-73 mmHg and 50-60 mmHg in AKI patients without hypertension. The range of MAPs and DBPs may be 70-80 mmHg and 54-62 mmHg in AKI patients with hypertension. The prognosis of sepsis with AKI was unaffected by MAP or DBP. Systolic blood pressure is not associated with sepsis in patients with AKI. Conclusions: To ensure renal perfusion, AKI patients with hypertension may require a higher MAP [70-80] versus (65-73), mmHg] and DBP [(54-62) vs (50-60), mmHg] than patients without hypertension.